Synthetic Talc and Talc‐Like Structures: Preparation, Features and Applications. Issue 3 (18th October 2017) - Claverie, Marie; Dumas, Angela; Carême, Christel; Poirier, Mathilde; Le Roux, Christophe; Micoud, Pierre; Martin, François; Aymonier, Cyril
Abstract: This contribution gives a comprehensive review about the progress in preparation methods, properties and applications of the different synthetic talc types: i) crystalline nanotalc synthesized by hydrothermal treatment; ii) amorphous and/or short‐range order nanotalc obtained by precipitation, and iii) organic–inorganic hybrid talc‐like structures obtained through a sol–gel process or a chemical grafting. Several advantages of nanotalc such as high chemical purity, high surface area, tunable submicronic size, high thermal stability, and hydrophilic character (leading to be the first fluid mineral) are emphasized. Synthetic nanotalc applications are also considered including its use as nanofiller in composite materials, as absorbers of organic compounds, as anticorrosion coatings and as agents for cosmetic applications. Regarding their high industrial application potential, intensive research has been carried out to better understand their behavior and develop processes to produce them. To facilitate further research and development, scientific and technical challenges are discussed in this Review article. Abstract : In the making : The growing interest in synthetic talc for polymer reinforcement and new cosmetic formulations has motivated research to propose novel synthesis routes based on the chemistry of materials. In this context, over the past 30 years, the synthesis process of talc has evolved noticeably leading to processes which could fulfill industrial requirements. In this Review, the different natures, the synthesis methods and the applications of synthetic nanotalc are enlightened with a focus on the crystalline nanotalc.